Integral Valorisation of Agri-Food By-Products Through the Production of Food Ingredients Using High-Pressure Thermal Treatments - Miriam Sánchez-Ordóñez; Jorge A. Saraiva; Carlos A. Pinto; Jonathan Delgado-Adámez; M. Rosario Ramírez-Bernabé (Foods)
This study investigates the production of stable ingredients with high bioactive compound content from agri-food wastes. For the valorization process, high-pressure thermal treatment (HPTT) at different temperatures (65, 75, and 85 °C) at 600 MPa for 5 min was applied to three by-products. These HPTTs were compared with conventional thermal treatments (TTs) carried out at the same temperatures and durations. The by-products studied were red pepper (RP) (Capsicum annuum), red wine pomace (RWP) from Tempranillo, and white wine pomace (WWP) from Cayetana, Pardina, and Montúa. Winemaking by-products presented higher fiber content compared to RP (RP 1.94%, RWP 38.14%, and WWP 34.46%). In RP, the color parameters such as lightness (L*) and redness (a*) were not significantly affected by HPTT or TT, and the total phenolic content (TPC), total carotenoid content (TCC), and antioxidant activity (ABTS) remained stable with the HPTT. The RWP and WWP were more sensitive to the HPTT, producing important color changes and reducing the bioactive compounds. Color (especially redness) showed positive correlations with TPC and ABTS, which could serve as a predictive indicator. Our study shows that HPTT can significantly improve the valorization of RP and winemaking by-products like pomace, leading to the production of a stable food ingredient characterized by high bioactive compound content.